2015
DOI: 10.1002/bit.25809
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating product inhibition in cellulase enzyme Cel7A

Abstract: Enzymes that degrade cellulose into glucose are one of the most expensive components of processes for converting cellulosic biomass to fuels and chemicals. Cellulase enzyme Cel7A is the most abundant enzyme naturally employed by fungi to depolymerize cellulose, and like other cellulases is inhibited by its product, cellobiose. There is thus great economic incentive for minimizing the detrimental effects of product inhibition on Cel7A. In this work, we experimentally generated 10 previously proposed site‐direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
(87 reference statements)
2
35
1
2
Order By: Relevance
“…The extensive hydrogen bond network between loop A4 R394 and the product +2 moiety supports its role in product inhibition. Mutation of R394 to alanine suppresses this network alleviating product inhibition . In contrast to previous observations, the product +2 glucosyl moiety is not hydrogen bonded to D259 .…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…The extensive hydrogen bond network between loop A4 R394 and the product +2 moiety supports its role in product inhibition. Mutation of R394 to alanine suppresses this network alleviating product inhibition . In contrast to previous observations, the product +2 glucosyl moiety is not hydrogen bonded to D259 .…”
Section: Resultscontrasting
confidence: 86%
“…The main chain D259 carbonyl group, however, forms a hydrogen bond with the O2 of the +1 glucosyl moiety (3.0 A) as previously reported [38]. D259A has been shown to mitigate product inhibition to a lesser extent than R394A or R251K [16]. The variability observed across structures in the hydrogen bond interactions between D259 and the product provides structural insight as to why this is the case.…”
Section: Product Interactionsmentioning
confidence: 52%
See 1 more Smart Citation
“…In experiments of integrated storage and microbial pretreatment, 25–50% of the cellulose was converted to glucose (Passoth et al 2013). Probably, even higher values of cellulose degradation might be possible when using simultaneous saccharification and fermentation, to avoid feedback inhibition of cellulase, and in general, by using improved enzyme cocktails (Atreya et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…On the mechanistic level, molecular origins of Cel7A's product inhibition remains controversial (Andric et al, ), and this uncertainty impedes engineering of variants that are less prone to inhibition. Such variants have been suggested on the basis of computational work (Bu et al, ; Silveira and Skaf, 2015), and most recently also produced by site directed mutagenesis (Atreya et al, ). This latter work confirmed that the predicted mutations alleviated product inhibition, but also found that this improvement was generally associated with reduced catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%